Impactos dos Eventos em Destinos Turísticos: um estudo de caso na cidade de Joinville, SC, Brasil - Scalabrini, Elaine Cristina Borges (2019)
The growth of tourism is remarkable in the global scenario and is a segment that has gained prominence is the business and events. Aiming to understand the events’ impacts, destinations have invested in researches. In this sense, realizing the lack of data about the events in the city of Joinville-SC, this study aims to understand their impacts in this destination. In order to attempt this aim, a quantitative survey was carried out, based on the application of questionnaires in seven events held in 2016. The results confirm the economic importance of the events for the municipality and point out that those responsible for the destination’s tourism planning must invest in basic and tourism infrastructure to attract events to Joinville, as well as to extend the stay of the participants.